Pengaruh Penggunaan Pupuk Kandang Dan Sistem Irigasi Alur Terhadap Ketersediaan Air Tanah Dan Pertumbuhan Cabai Merah (Capsicum Annuum L.) - Nofianti Zebua; Natalia Kristiani Lase (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to determine the impact of the use of manure and furrow irrigation system on soil water availability and the growth of red chili plants (Capsicum annuum L.). In Indonesia, agricultural land often experiences problems such as soil degradation and water scarcity, which affect crop yields. Therefore, it is important to find solutions based on sustainable agriculture, such as the use of organic fertilizers and more efficient irrigation techniques. This research method is based on a review of previous studies, using a literature study approach. The data collected came from literature sources, through the process of reading, recording and organizing research materials. The data sources are taken from journals or articles that have existed before and books related to agriculture. The results showed that the application of manure and furrow irrigation significantly increased soil moisture and plant growth compared to the control treatment. This finding is in accordance with several previous studies, such as those conducted by Sitorus and Tyasmoro (2019), Dewi et al. (2020), and Arifin (2021).